2004
DOI: 10.1038/ncb1099
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine tract-binding protein promotes insulin secretory granule biogenesis

Abstract: Pancreatic beta-cells store insulin in secretory granules that undergo exocytosis upon glucose stimulation. Sustained stimulation depletes beta-cells of their granule pool, which must be quickly restored. However, the factors promoting rapid granule biogenesis are unknown. Here we show that beta-cell stimulation induces the nucleocytoplasmic translocation of polypyrimidine tract-binding protein (PTB). Activated cytosolic PTB binds and stabilizes mRNAs encoding proteins of secretory granules, thus increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
175
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(184 citation statements)
references
References 41 publications
6
175
2
1
Order By: Relevance
“…Both glucose and GLP-1 stimulate nucleocytoplasmic translocation of PTB1 in INS-1 cells (Knoch et al, 2006). Cytosolic PTB1 quickly upregulates the expression of insulin and the secretory vesicle protein ICA512 a receptor tyrosine proteinphosphatase-like protein associated with insulin secretory vesicles (Knoch et al, 2004). Knoch and colleagues also uncovered a PKA-dependent phosphorylation of PTB1 in INS-1 cells.…”
Section: Stabilization Of the Insulin Mrna Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Both glucose and GLP-1 stimulate nucleocytoplasmic translocation of PTB1 in INS-1 cells (Knoch et al, 2006). Cytosolic PTB1 quickly upregulates the expression of insulin and the secretory vesicle protein ICA512 a receptor tyrosine proteinphosphatase-like protein associated with insulin secretory vesicles (Knoch et al, 2004). Knoch and colleagues also uncovered a PKA-dependent phosphorylation of PTB1 in INS-1 cells.…”
Section: Stabilization Of the Insulin Mrna Transcriptmentioning
confidence: 99%
“…Polypyrimidine tract binding protein (PTB) binds to the U-rich polypyrimidine tract of mRNAs encoding insulin and insulin secretory vesicle proteins thereby stabilizing them (Knoch et al, 2004;Knoch et al, 2006;Tillmar et al, 2002). Both glucose and GLP-1 stimulate nucleocytoplasmic translocation of PTB1 in INS-1 cells (Knoch et al, 2006).…”
Section: Stabilization Of the Insulin Mrna Transcriptmentioning
confidence: 99%
“…It is now widely believed that PTB functions as a negative regulator of pre-mRNA splicing, blocking the inclusion of numerous alternative exons into mRNA (Black, 2003), including its own exon . Besides roles in splicing, PTB has also been implicated in the regulation of other aspects of RNA metabolism, such as premRNA polyadenylation (Castelo-Branco et al, 2004), mRNA stability (Kosinski et al, 2003;Knoch et al, 2004), mRNA export from the nucleus (Zang et al, 2001) and mRNA localization in the cytoplasm (Cote et al, 1999). In addition, PTB is involved in the control of cap-independent translation driven by the internal ribosomal entry site (IRES).…”
Section: Introductionmentioning
confidence: 99%
“…Here it was shown that glucose stimulated PTB phosphorylation by PKA is mediated by increased cAMP levels and that this was potentiated by the glucagon-like peptide 1. (Knoch et al, 2004;Knoch et al, 2006). In one of these studies more or less the entire pool of PTB was exported into the cytoplasm in response to stimulation with a high glucose concentration.…”
Section: Page 5 Of 14mentioning
confidence: 99%
“…Indeed, PTB was recently shown to bind this sequence thereby mediating increased preproinsulin mRNA stability and levels . Interestingly, PTB has been demonstrated to bind similar pyrimidine-rich sequences located to the 3'-UTR regions of other insulin granule proteins, such as ICA512, PC1/3 and PC2, indicating that the biosynthesis of secretory granule proteins in general is controlled by one unifying mechanism (Knoch et al, 2004). …”
Section: Ptb and Preproinsulin Mrna Stabilitymentioning
confidence: 99%